Capsule optoacoustic endoscopy for esophageal imaging. Issue 10 (25th June 2019) - He, Hailong; Stylogiannis, Antonios; Afshari, Parastoo; Wiedemann, Tobias; Steiger, Katja; Buehler, Andreas; Zakian, Christian; Ntziachristos, Vasilis
Abstract: Detection and monitoring of esophageal cancer severity require an imaging technique sensitive enough to detect early pathological changes in the esophagus and capable of analyzing the esophagus over 360 °in a non‐invasive manner. Optoacoustic endoscopy (COE) has been shown to resolve superficial vascular structure of the esophageal lumen in rats and rabbits using catheter‐type probes. Although these systems can work well in small animals, they are unsuitable for larger lumens with thicker walls as required for human esophageal screening, due to their lack of position stability along the full organ circumference, sub‐optimal acoustic coupling and limited signal‐to‐noise ratio (SNR). In this work, we introduce a novel capsule COE system that provides high‐quality 360° images of the entire lumen, specifically designed for typical dimensions of human esophagus. The pill‐shaped encapsulated probe consists of a novel and highly sensitive ultrasound transducer fitted with an integrated miniature pre‐amplifier, which increases SNR of 10 dB by minimizing artifacts during signal transmission compared to the configuration without the preamplifier. The scanner rotates helically around the central axis of the probe to capture three‐dimensional images with uniform quality. We demonstrate for the first time ex vivo volumetric vascular network images to a depth of 2 mm in swine esophageal lining using COE. Vascular information can be resolved within the mucosa and submucosa layers as confirmed by histology of samples stained with hematoxylin and eosin and with antibody against vascular marker CD31. COE creates new opportunities for optoacoustic screening of esophageal cancer in humans. Abstract : In this work, we introduce a novel capsule optoacoustic endoscopy (COE) system that provides high‐quality 360‐degree images of the entire lumen, specifically designed for typical dimensions of human esophagus. The pill‐shaped encapsulated probe consists of a novel and highly sensitive ultrasound transducer fitted with an integrated miniature pre‐amplifier. We demonstrate for the first time ex vivo volumetric vascular network images to a depth of 2 mm in swine esophageal lining using COE.